Remaining Service Life Struktur Conveyor C pada Tambang Batubara PT XYZ di Kabupaten Tanah Laut, Provinsi Kalimantan Selatan - Muhammad Fedryana; Elfida Moralista; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2022)
Abstract. Conveyors made of steel with a mixture of carbon are prone to corrosion which can cause damage so that it will reduce the remaining service life of the conveyor structure. Therefore, corrosion control is carried out using the coating method to prevent corrosion from occurring, so as to get the service life of the conveyor structure according to the expected specifications.The research was conducted on a 90 meter long conveyor structure divided into 3 segments which were installed in 2014 and inspected in 2019, having a service life specification of 5 years and a design life of 15 years. This study aims to determine the type of corrosion that occurs, to control corrosion, to determine the corrosion rate and the remaining service life of the conveyor structure. The research method used is the measurement of thickness reduction on the conveyor structure using the Thickness Gauge TT 130, supported by supporting data in the form of environmental data for the period 2017 - 2021 in the form of rainfall data with an average of 252,7 mm/year, air temperature with an average of 28,050C and relative humidity with an average of 83,10%. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion rate on the conveyor structure ranges from 0.362-0.370 mm/year into the good category based on the relative corrosion resistance of steel. The remaining service life ranges from 4,880 - 11,780 years with a service life of 5 years, thus there are 14 test points (56%) that reach the design life and 11 test points (44%) that do not reach the design life of 15 years. Abstrak. Conveyor yang berbahan dasar baja dengan campuran karbon rawan mengalami korosi yang dapat menyebabkan kerusakan sehingga akan mengurangi sisa umur pakai pada struktur conveyor. Maka dari itu, dilakukan pengendalian korosi menggunakan metode coating untuk mencegah agar tidak terjadi korosi, sehingga mendapatkan usia pakai struktur conveyor sesuai spesifikasi yang diharapkan.Penelitian dilakukan pada struktur conveyor sepanjang 90 meter terbagi menjadi 3 segmen yang dipasang pada tahun 2014 dan dilakukan inspeksi pada tahun 2019, mempunyai spesifikasi umur pakai selama 5 tahun dan umur desain selama 15 tahun. Penelitian bertujuan untuk mengetahui jenis korosi yang terjadi, melakukan pengendalian korosi, mengetahui laju korosi dan sisa umur pakai pada struktur conveyor. Metode penelitian yang digunakan yaitu pengukuran pengurangan ketebalan pada struktur conveyor menggunakan alat Thickness Gauge TT 130, dengan ditunjang menggunakan data pendukung berupa data lingkungan selama periode tahun 2017 - 2021 berupa data curah hujan dengan rata-rata 252,7 mm/tahun, temperatur udara dengan rata-rata 28,050C dan kelembapan relatif dengan rata-rata 83,10%. Jenis korosi yang terjadi pada struktur conveyor yaitu korosi merata. Laju korosi pada struktur conveyor berkisar antara 0,362-0,370 mm/tahun masuk kedalam kategori good berdasarkan ketahanan korosi relatif baja. Sisa umur pakai berkisar antara 4,880 - 11,780 tahun dengan umur pakai selama 5 tahun, dengan demikian terdapat 14 test point (56%) yang mencapai umur desain dan 11 test point (44%) yang tidak mencapai umur desain yaitu 15 tahun.